The Effect of Massage on the Cardiac Autonomic Nervous System and Markers of Inflammation in Night Shift Workers: a Pilot Randomized Crossover Trial - Fazeli, MD, PhD, Mir Sohail; Pourrahmat, BSc, Mir-Masoud; Massah, MD, Golshan; Lee, BSc, Kelsey; Lavoie, MD, PhD, Pascal M.; Fazeli, MD, Mirfarhang; Esser, RMT, Alison; Collet, MD, PhD, Jean-Paul (International Journal of Therapeutic Massage & Bodywork, 2020)
Background: Shift work is a necessary part of many industries; however, it can have detrimental effects on health over time. Purpose: This study investigated the effect of a massage intervention on the cardiac autonomic activity and blood inflammatory markers of healthy medical residents working night shifts. Setting: This trial was conducted at British Columbia Children’s and Women’s Hospital between February 2014 and June 2016. Participants: Included participants were generally healthy medical residents and were working rotating night shifts on a regular basis. Research Design: This was a randomized, controlled, crossover, open-label trial (NCT02247089). Interventions: Participants received either a 30-min massage intervention or reading control after consecutive periods of night shift. Main Outcome Measures: The primary outcome was high frequency, a proxy for the cardiac parasympathetic activity, measured via heart rate variability. Secondary outcomes included other heart rate variability measures, blood markers of inflammation, and blood pressure. Results: Twelve participants were recruited (nine female) with median age of 28 years. There was no significant difference between the massage intervention and the reading control for the primary outcome, (median relative change between pre- and postmassage [interquartile range]: 62% [-1 to 150], pre- and postreading: 14% [-10 to 51], p = .16). Similarly, there was no difference with respect to blood inflammatory markers and blood pressure. Median high frequency significantly increased between pre- and postmassage (185 vs. 358 ms2, p = .04). Conclusion: This pilot study found no statistically significant difference between the massage intervention and the reading control; however, we did observe a significant increase in median high frequency from before massage to after massage, indicative of increased parasympathetic activity. This study may help inform planning of larger trials evaluating massage interventions on the activity of the autonomic nervous system and managing shift work stress.